Retrospective study on imported schistosomiasis in Morocco between 2005 and 2017. (October 2020) - Balahbib, Abdelaali; Amarir, Fatima; Bouhout, Souad; Adlaoui, El Bachir; Rhajaoui, Mohamed; Sadak, Abderrahim
Since 2004, no indigenous cases of schistosomiasis have been found in Morocco; only imported cases have been detected. The aim of the present study was to describe and analyse the epidemiological profile of imported schistosomiasis between 2005 and 2017, and, by this, attract attention to the probability of a reintroduction of this disease. During this period, 27 cases were recorded in Morocco, with a male predominance (13:1). All cases reported were found among African immigrants from Mauritania (37%), Mali (18%) and Senegal (15%).   Schistosoma heamatobium was the most dominant specie. Most cases were reported in Rabat and Agadir, where there are many snail habitats. To prevent a re-emergence of the disease, the main challenge would be to consolidate and maintain a sustainable surveillance and control system of the importation of bilharzia. The frequency of asymptomatic schistosomiasis justifies a systematic health check-up for all travellers, migrants and immigrants.